Segodnia v mire . Segodnia v mire . The World Today . Сегодня в мире - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. "Day of Peace" celebrations; the United Nations (UN) meeting and discussion on current topics. Featured in the program: Pérez de Cuéllar, Javier (Secretary General of the United Nations) Contributors: Korzin, Valerii (Anchor) Series description: An information program of the Central Television of the USSR (CT USSR). The hosts were Igor Fesunenko, Valentin Zorin, Farid Seiful-Muliukov, and others. The program was first broadcasted on December 1, 1978 and was broadcasted until 1988. Репортажи: празднование Дня Мира, заседание ООН и обсуждение горячих точек. В программе участвуют: Перес де Куэльяр, Хавьер (Генеральный секретарь OOН) Создатели: Корзин, Валерий (Ведущий/Ведущая) Описание серии: Информационная телепередача Центрального телевидения СССР. Ведущие — Игорь Фесуненко, Валентин Зорин, Фарид Сейфуль-Мулюков и другие. Первый выпуск передачи вышел в эфир 1 декабря 1978 года. Выходила до 1988 года